Analysis Of Patient Satisfaction On The Quality Of Service (HEALTH CARE: JURNAL KESEHATAN, 2024)
The level of satisfaction from the quality of service depends on the expectations of the community. One of the government's efforts in measuring the performance of public services is to compile an index of community satisfaction with public services that has been established through the RI MENPAN regulation number Kep/25/M.PAN/2/2004 concerning Guidelines for compiling a community satisfaction index. This study aims to find out the analysis of patient satisfaction on the quality of service in the Inpatient Installation Room of the Sekayu Regional General Hospital in 2023. It will be carried out in May - June 2022. This is a quantitative research with a cross-sectional design, the population of this study is the number of patient visits in the Inpatient Installation room RUD Sekayu, totaling 1470 patients, a sample of 94 respondents. Collection and retrieval of data using a questionnaire. The results of the statistical test analysis used the Chi-Square statistical test and multiple logistic regression where the results showed that there was a significant relationship (p value